Dielectric and loss properties of MnZn ferrites at high frequency - Zhu, Jun. (2008)
In this thesis, a new combined polarization model is proposed for the analysis of the permittivity spectrum of MnZn ferrite at high frequencies. This model uses thermal ion polarization and interface space charge polarization simultaneously to stimulate the variance of permittivity against frequency in MnZn ferrite.